0049 Association between work exposure, alcohol intake, smoking and Dupuytren's disease in a large cohort study (Gazel). (23rd June 2014) - Descatha, Alexis; Carton, Matthieu; Mediouni, Zakia; Dumontier, Christian; Roquelaure, Yves; Goldberg, Marcel; Zins, Marie; Leclerc, Annette
Abstract : Objectives: In view of the debate about biomechanical and toxic factors in Dupuytren's disease, we aimed to describe its relationship with certain occupational factors and alcohol intake and smoking. Method: Subjects in the French GAZEL cohort answered a questionnaire in 2012 included self-reported Dupuytren's disease, such as disabling Dupuytren's disease (including surgery). In 2007, self-assessed lifetime occupational biomechanical exposure was recorded (carrying loads, manipulating a vibrating tool, climbing stairs), as well as alcohol intake, smoking and diabetes mellitus. Analyses were performed on high alcohol intake, smoking and duration of relevant work exposure, stratified by gender for both outcomes. Results: A total of 13 587 subjects answered the questionnaire in 2012 (73.7% of the questionnaire sent) and constituted the sample (10 017 men and 3570 women, aged from 64 to 73 years; mean age for men 68 years and for women 65 years). Among men age, diabetes, heavy drinking and over 15 years of manipulating a vibrating tool at work were significantly associated with Dupuytren's disease; except for diabetes, the association with these factors was stronger for disabling Dupuytren's disease (or surgery). Among the 3570 women included, 160 reported Dupuytren's disease (4.5%). The number of cases in the group of women was too low to reach conclusions, although the findings seemed similar for age, diabetes and vibration exposure. Conclusions: In this large French cohort study, Dupuytren's disease in men was associated with high levels of alcohol consumption and exposure to hand-transmitted vibration. It is likely that the same applied to women.